Global climate dynamics and Plio-Pleistocene paleoenvironments of northwestern Peru - Campbell, Kenneth (2010)
Northwestern Peru lies near the transition zone between climate systems of the southern and northern hemispheres. As a result, in the modern era climate anomalies known as El Niño-Southern Oscillation (ENSO) have a dramatic effect on this region, bringing intense, monsoonal-type rains to what is normally a semi-arid to arid environment. Data from deep-sea cores suggest that during the early Pliocene the ENSO condition was more or less permanent, rather than an anomaly. Other data also show that the transition zone between the two hemispheric climate systems, the Inter-tropical Convergence Zone (ITCZ), occurs farther south during ENSO events. Although it is not known whether ENSO triggers movement of the ITCZ, or vice versa, it is the more southerly position of the ITCZ that brings the monsoon rains to northwestern Peru because of the changes it brings to the direction of flow of the trade winds. Regardless of the ultimate cause, a long-term ENSO condition would have had a dramatic effect on paleoenvironments of northwestern Peru. Rather than deserts, the landscape would have been covered in forests, and year-around streams probably flowed from the coastal mountains. Evidence for such paleoenvironments in the region is seen in Pleistocene fossil deposits, especially those of the upper Pleistocene Talara Tar Seeps. Many taxa occur in these deposits that could not survive in the region today, suggesting that ENSO conditions were common in the late Pleistocene. Terrestrial data in support of a permanent, early Pliocene ENSO condition are still unavailable, but finding such data and correlating the timing of ENSO events in northwestern Peru with climatic events in other parts of South America, and globally, is important because as we enter a period of great uncertainty regarding global climate change, it is possible that northwestern Peru will experience dramatic changes in climate.